2016
DOI: 10.1186/s12977-016-0323-4
|View full text |Cite|
|
Sign up to set email alerts
|

Are T cells the only HIV-1 reservoir?

Abstract: Current antiretroviral therapies have improved the duration and quality of life of people living with HIV-1. However, viral reservoirs impede complete eradication of the virus. Although there are many strategies to eliminate infectious virus, the most actively pursued are latency reversing agents in conjunction with immune modulation. This strategy, known as “shock and kill”, has been tested primarily against the most widely recognized HIV-1 latent reservoir found in resting memory CD4+ T cells. This is in par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 132 publications
1
70
0
2
Order By: Relevance
“…A number of studies have shown various cell types in the liver are permissive to HIV infection in vitro including HSC [147] , Kupffer cells [148, 149] and hepatocytes [150, 151] . HIV infection of these cells has also been demonstrated in vivo in individuals naïve to ART [152, 153] and HIV sequences from the liver in individuals off ART have distinct compartmentalised sequences when compared to other tissue sites [154] .…”
Section: Pathogenesismentioning
confidence: 99%
“…A number of studies have shown various cell types in the liver are permissive to HIV infection in vitro including HSC [147] , Kupffer cells [148, 149] and hepatocytes [150, 151] . HIV infection of these cells has also been demonstrated in vivo in individuals naïve to ART [152, 153] and HIV sequences from the liver in individuals off ART have distinct compartmentalised sequences when compared to other tissue sites [154] .…”
Section: Pathogenesismentioning
confidence: 99%
“…The use of whole blood was motivated by several factors: 1) it allowed comparison to the only other studies of host gene regulatory responses to nonpathogenic SIV infection, as they also used whole blood (Bosinger et al 2009;Jacquelin et al 2009;Lederer et al 2009), 2) whole blood is superior to PBMCs for transcriptomic analysis when storage is required as was the case for our study (Debey-Pascher et al 2011), 3) global transcriptomic profiles from whole blood account for latent SIV reservoirs, and may therefore be better for understanding immune responses to SIV infection (Kandathil et al 2016), and 4) ISG gene expression profiles of SIVinfected SMs are largely concordant between whole blood and the lymph node (an important site of immune activity in response to SIV/HIV infection), enabling accurate inference of the broad transcriptomic responses to infection conserved between lymph nodes and whole blood (Bosinger et al 2009).…”
Section: Study System and Sample Collectionmentioning
confidence: 98%
“…[144] However, T follicular helper cells (T fh ) have also been proposed as a major cellular reservoir, [145] and non-T cell reservoirs have also been suggested. [146] The cells comprising the reservoir can be found in many areas of the body, particularly the peripheral blood, lymph nodes, and the gut. [147] An additional subject of debate is whether low-level replication continues during cART, [148] leading to the possibility that both latency and low-level replication contribute to HIV persistence.…”
Section: Targeting Hiv Latencymentioning
confidence: 99%